A universal relation approach for natural query in logic database system - Selamat, Harihodin (Penerbit UTM Press, 1992)
Recent advances in Artificial Intelligence and Relational Database systems have contributed to the development of Logic Database systems. A lot of research in logic database have been encompassed on the query evaluation and optimization techniques. Very litde effort has been put to the development of the user's query system to facilitate the naive users interacting with the database. Currently, the form of query is based on the primitive logic form. Therefore, this project aims at developing a prototype natural query system to the logic database as a compromise between the primitive logic query and the natural language query systems. This paper describes a conceptual framework of the natural query system. The concept of predicate universal relation is introduced as an interface to bridge the natural query and the corresponding primitive logic query. The concept of data types is employed as a tool towards the construction of the predicate universal relation. We believe this is the first attempt towards a natural query system for logic database via a universal relation approach.